Development Of Student Character Based On Values Of Islamic Religious Education - Saihul Atho` Alaul Huda; Zendy Pradana (SCHOOLAR: Social and Literature Study in Education, 2023)
Education is one of the factors forming one's religiosity. Education in schools, especially religious education, has a very large role in shaping one's religiosity. The religious experience he gained (had done) at school has a considerable impact on one's religious practice in everyday life. At MAN 3 Jombang the students are also well educated according to the study of the yellow book, so they have good personalities and morals. MAN 3 Jombang always supports and facilitates its students to always excel in both academic and non-academic fields. The purpose of this study was to find out the character formation of students at MAN 3 Jombang. As well as what concepts are used in character building, this can be seen from every activity carried out there, starting from entering class, dressing, behaving. The method used in collecting data by means of observation, interviews, and nd documentation using a descriptive qualitative approach.